Growth Responses of Organic Tomato Seedlings to N Liquid Fertilizers and Compost-Amended Growing Media. Issue 1 (2nd January 2017) - Abdelrahman, H. M.; Ceglie, F. G.; Awad, F. A.; Tittarelli, F.
ABSTRACT: This work evaluated the response of organic tomato seedlings to locally produced compost-amended growing media and commonly used N liquid fertilizers. Green (GC) and mixed (MC) composts were used in growing media formulation with 70, 45, 20, and 0% (control based on peat) on volume basis for organic tomato seedling growth. Three locally available N liquid fertilizers, hydrolyzed-protein-based fertilizer (HP), blood-meal-based fertilizer (BM), and algae-extract-based fertilizer (AE), were tested. Seedlings were evaluated 34 days after sowing for plant height; stem diameter; shoot weights; sturdiness index; specific leaf area; and N, P, and K contents in the seedlings shoot. The statistical analysis showed that the substrate type, fertilizer, and their interaction significantly ( p ≤ 0.05) affected, in most cases, the seedlings growth. The compost, especially with 20 or 45% amended substrate, produced longer seedlings with thicker diameter, greater fresh and dry weights, and greater leaves number compared to the control (compost-free) substrate. The use of the HP or the AE fertilizer generally contributed to better seedlings growth than did the BM-based fertilizer. The HP fertilizer clearly affected ( p ≤ 0.01) the seedling diameter, fresh weight, and leave numbers while the AE fertilizer affected clearly seedling sturdiness index. The use of the GC or MC compost complemented with the HP or the AE fertilizer successfully reduced up to 45% of peat use in growing media and produced robust organic tomato seedlings.